Study the Effect of Some Physical and Chemical Agents on Growth of Enterobacter Sazkazakii Isolated from Local Foods - Shafeek, May H (Al-Nahrain Journal of Science, 2011)
This research was performed to study the effect of some physical & chemical material which found domestically in order to control the growth of E. sakazakii. The effect of different concentrations of NaCl exhibit that 3.5% of the salt killed the bacteria after 30 min of incubation, while the low concentration showed a less inhibition in numbers of cells. In using different concentrations of chlorine showed that 6% concentration was effective in killing the bacteria in 10 min, while 9% conc. destroyed the bacteria in 5 min. when using different conc. of citric acid reaching pH: 5 & 3 bacterial growth inhibited to low levels in comparing the control. And when we use NaOH to gain a pH: 9 & 11 bacterial growth were inhibited to 40 & 25 colony forming unit/ml after 30 min. of incubation.